Estudo da relação das espécies reativas de oxigênio, glutamato e medicação antioxidante com situações de dor crônica, dor aguda ou ausência de dor em seres humanos - Tulio Vinicius de Oliveira Campos (2015)
Introduction: Investigation of chronic pain mechanisms and analgesia constitute a promising research field. Recent studies attribute to reactive oxygen species (ROS) and glutamate (GLU) a central role in pain modulation. Our study aims to evaluate the relationship amongserum and cerebrospinal fluid (CSF) ROS, CSF GLU, chronic/acute or no pain situations. In addition, we assessed the treatment of chronic pain by an antioxidant medication and influences on serum levels of ROS.Methods: Forty patients were distributed according to pain symptoms: chronic (n = 15), acute (n = 12) and no pain (n = 13). Pain was assessed by visual analogue scale (VAS) and WOMAC index (Western Ontario and McMaster Universities Osteoarthritis Index). ROS was measured by DCHF-DA essay. Statistical analysis employed Prism 5 software for Windows. Fourteen patients with knee osteoarthritis and chronic pain have taken antioxidant medication for three months. VAS, WOMAC and ROS serum levels were registered before and after treatment.Results: Analysis of maximum fluorescence and DCHF-DA curve inclination for peripheral blood and cerebrospinal fluid samples did not reveal difference among chronic, acute and no pain groups. Comparison of glutamate levels in CSF samples showed a statistically significantdifference between acute pain and the other groups. Patients who took an antioxidant medication for three months showed improvement in VAS and WOMAC index, but there was no correspondence in ROS levels. Linear correlation analysis suggested a better response in VAS for patients with long lasting pain complains. Conclusions: Higher cerebrospinal fluid GLU levels were identified in acute pain group. The antioxidant medication reduced pain in chronic group.